Case report: Right coronary artery rupture—A rare complication of cardiopulmonary resuscitation - Ai, Chenchen; Lv, Xiaobo; Qi, Xuehong; Tang, Hanbo (Frontiers in Cardiovascular Medicine, 2022)
An 8-month-old female experienced a life-threatening right coronary artery rupture resulting from cardiopulmonary resuscitation (CPR) 1 week after corrective surgery for Tetralogy of Fallot (TOF). Emergency exploratory thoracotomy was performed due to uncorrectable hemorrhagic shock. During exploration, active bleeding was detected in the anterior branch of the right ventricular coronary artery. After the repair, the patient's condition improved. Coronary artery rupture is an extremely rare complication of CPR. Here, we present a case that provides new reflections and warnings to clinicians.